Development of control system in abdominal operating ROV - ZHANG Weikang; WANG Guanxue; XU Guohua; LIU Chang; SHEN Xiong (Zhongguo Jianchuan Yanjiu, 2017)
In order to satisfy all the requirements of Unmanned Underwater Vehicle(UUV)recovery tasks, a new type of abdominal operating Remote Operated Vehicle(ROV) was developed. The abdominal operating ROV is different from the general ROV which works by a manipulator, as it completes the docking and recovery tasks of UUVs with its abdominal operating mechanism. In this paper, the system composition and principles of the abdominal operating ROV are presented. We then propose a framework for a control system in which the integrated industrial reinforced computer acts as a surface monitor unit, while the PC104 embedded industrial computer acts as the underwater master control unit and the other drive boards act as the driver unit. In addition, the dynamics model and a robust H-infinity controller for automatic orientation in the horizontal plane were designed and built. Single tests, system tests and underwater tests show that this control system has good real-time performance and reliability, and it can complete the recovery task of a UUV. The presented structure and algorithm could have reference significance to the control system development of mobile robots, drones, and biomimetic robot.